Meningkatkan Pemahaman Konsep Siswa Kelas XI-IPS dalam Belajar Matematika melalui Metode Guided Discovery Instruction [Improving Conceptual Understanding of Grade XI Social Science Students in Learning Mathematics Using the Guided Discovery Instruction Method] - Dessy Rahmawati; Melda Jaya Saragih (Universitas Pelita Harapan, 2016)
The aim of this research was to know whether the Guided Discovery Instruction (GDI) method can improve conceptual understanding in learning mathematics. The research method used classroom action research in two cycles. The pre-cycle showed that students' conceptual understanding still was low. The research was conducted at Sekolah Lentera Harapan (SLH) in Ambon involving 14 students and the instruments used were post-test questionnaires, attainment sheet method, interviews, observations, and journal reflections. The results showed that using GDI improved students’ conceptual understanding in learning mathematics as evident by the increased number of students graduating KKM (71) from the first cycle (71.4%) to the second cycle (85.7%).BAHASA INDONESIA ABSTRAK: Penelitian bertujuan mengetahui peningkatan pemahaman konsep siswa melalui metode GDI dengan model penelitian tindakan kelas yang dilakukan dalam dua siklus. Pra-siklus untuk memastikan pemahaman konsep kelas XI-IPS masih rendah. Penelitian ini dilakukan pada kelas XI-IPS SLH Ambon melibatkan 14 siswa dan menggunakan post-test, angket, lembar ketercapaian metode, wawancara, observasi, angket, dan jurnal refleksi sebagai instrumen. Hasilnya menunjukkan GDI meningkatkan pemahaman konsep siswa terlihat dari peningkatan jumlah siswa lulus KKM (71) dari siklus I (71,4%) ke siklus II (85,7%).